Influence of alexithymia severity in the healthy population on the susceptibility to false interoceptive feedback - Hitomi Ikarashi; Hitomi Ikarashi; Naofumi Otsuru; Naofumi Otsuru; Sena Takahashi; Kazuaki Nagasaka; Kazuaki Nagasaka; Masayuki Hara; Hideaki Onishi; Hideaki Onishi (Frontiers in Psychology)
Alexithymia is a psychological trait characterized by difficulty expressing emotions. Previous studies reported that individuals with higher alexithymia have a decreased sense of interoception, which is the sense of monitoring and controlling internal organs. Thus, we hypothesized that internal organ activity (cardiac activities in the present study) was easily affected by false feedback in individuals with severe alexithymia. Therefore, we investigated whether the effects of fake heart rate feedback on real cardiac activities differ depending on the severity of alexithymia as assessed by the 20-item Toronto Alexithymia Scale (TAS-20). Fake heart rate feedback was presented as if it were occurring in the individual’s hand through a virtual reality system at various speeds. Changes in cardiac activities were evaluated by the root-mean-square-successive difference (RMSSD, high value indicates greater parasympathetic tone) of the heartbeat interval. Our findings revealed a negative correlation between externally oriented thinking, a subscale of the TAS-20 score, and the RMSSD change ratio elicited by fake heart rate feedback. These findings indicate that individuals with higher alexithymia might be particularly susceptible to external fake feedback.